2012
DOI: 10.1371/journal.pone.0051740
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Domestic Violence and Mental Disorders: A Systematic Review and Meta-Analysis

Abstract: BackgroundLittle is known about the extent to which being a victim of domestic violence is associated with different mental disorders in men and women. We aimed to estimate the prevalence and odds of being a victim of domestic violence by diagnostic category and sex.MethodsStudy design: Systematic review and meta-analysis. Data Sources: Eighteen biomedical and social sciences databases (including MEDLINE, EMBASE, PsycINFO); journal hand searches; scrutiny of references and citation tracking of included article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
428
1
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 592 publications
(483 citation statements)
references
References 63 publications
35
428
1
19
Order By: Relevance
“…A recent systematic review including 41 studies, reported a higher risk of experiencing IPV in women with depressive disorders (OR ¼ 2.77; 95% CI ¼ 1.96-3.92), anxiety disorders (OR ¼ 4.08; 95% CI ¼ 2.39-6.97), and PTSD (OR ¼ 7.34; 95% CI ¼ 4.50-11.98), as compared to women without mental disorders (Trevillion, Oram, Feder, & Howard, 2012).…”
Section: What Are the Common Health Consequences?mentioning
confidence: 99%
“…A recent systematic review including 41 studies, reported a higher risk of experiencing IPV in women with depressive disorders (OR ¼ 2.77; 95% CI ¼ 1.96-3.92), anxiety disorders (OR ¼ 4.08; 95% CI ¼ 2.39-6.97), and PTSD (OR ¼ 7.34; 95% CI ¼ 4.50-11.98), as compared to women without mental disorders (Trevillion, Oram, Feder, & Howard, 2012).…”
Section: What Are the Common Health Consequences?mentioning
confidence: 99%
“…Women survivors of intimate partner violence (IPV) are at increased risk of mental ill health including depression and post-traumatic stress disorder (PTSD) [17], notwithstanding the fact that the relationship of IPV and mental ill health may be bidirectional [39]. Mental ill health among women has also been partially explained by pathways from other violent exposures, including histories of childhood physical and/or sexual abuse, rape by non-partners or other life traumatic events such as near-death experiences or being victims of crimes [8,1013].…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of domestic violence worldwide and the severity of its impact on women's mental health (12)(13)(14) justifies testing whether these two phenomena jointly contribute to the explanatory models of HFI. The relevance of HFI per se, combined with the apparent inability of theoretical models confined to addressing socio-economic issues to fully consider the complexities involved, indicate that more studies are needed.…”
mentioning
confidence: 99%